Study on Influence of Environmental Effect on Birth Weight, Weaning Weight and Daily Growth of Baluchi Sheep - Saghi, D.A.; Khadivi, H.; Navidzadeh, M.; Nikbakhti, M. (Pakistan Journal of Nutrition, 2007)
This study investigates different environmental effects on birth and weaning weight and daily growth of Baluchi lambs. For this purpose, we analyzed 10680 records that collection within a period of 21 years (1983-2003) in Abbasabad Sheep Breeding Station, located in northeast of Mashhad, Iran. Three different statistical models with considering effects of flock, litter size, sex, ewe age in parturition, lamb age in weaning weight and their interaction were used for parameters measurement. Except for effect of flock on weaning weight and daily growth, other effects were significant (p